ANALISIS KELENGKAPAN PENGISIAN LEMBARAN RINGKASAN MASUK DAN KELUAR REKAM MEDIS RAWAT INAP KSM ILMU KESEHATAN ANAK GUNA MENUNJANG MUTU REKAM MEDIS DI RSUP DR HASAN SADIKIN BANDUNG - Encep Hada; Neni Rohaeni; Luqmanul Hakim; Wowo Trianto; Ayu Hendrati Rahayu (UPPM Politeknik TEDC Bandung, 2019)
Completeness of filling medical record summary sheets primarily in and out is one of the indicators of medical record quality. This research aims to know the description of the completeness of the summary sheet in and outpatient medical record inpatient internal medicine to support the quality of the medical record in a general hospital area RSUP Dr. Hasan Sadikin Bandung. The research method used is descriptive research method. Research on data collection techniques: observation, interviews, documentation and library studies. The results showed that the completeness of the summary sheet in and out conducted by the authors obtained the percentage of completeness of charging for the months of January and February Year 2019 with a total 228 medical record file is 175 (77%) and for the incompleteness of filling of 53 (23%). The authors suggest to the hospital that: (1) Carry out the completion of the incoming and outgoing hospital outpatient submission sheets must be in accordance with the operational standards of the established procedure. (2) Increased coordination to all room officers of physicians and nurses or personnel concerned about the importance of completeness and filling in medical records. (3) Creating incomplete data on filling in incoming and outgoing summary sheets to be presented to the relevant physician.